Kamenica Castle in Croatia Zagorje region - Krešimir Regan (Studia Lexicographica)
This paper examines the centuries-long history of the castle Kamenica, situated above the identically named settlement in the Croatian Zagorje region, not far from Lepoglava. It was first mentioned in writing in 1311. It was built in the second half of the 13th century at the latest, by an unknown Zagorje noble, as a fortified residence and centre of the identically named estate. Between 1399 and 1405, Kamenica became the property of Herman II of Celje, whose descendants held it until 1456. Although no source directly mentions the fall of Kamenica, it likely happened during the war for the Celje succession, and the castle was first mentioned as a ruin in 1459, when King Matthias Corvinus donated it to John Vitovac. During the time it was under the Vitovacs (1459–88), Kamenica was permanently abandoned, and its holdings were combined with the neighbouring Trakošćan estate into the joint Trakošćan-Kamenica estate, which was formally seated in Trakošćan, but factually in the fortified manor Klenovnik. The existing, meagre architectural elements suggest Kamenica was a small castle (castrum) dating from the second half of the 13th century. It consisted of a trapezoidal core at the top of a steep, conical eminence, formed of a walled, fortified house with a smallish courtyard protected by a wooden palisade, and a fortified, circular suburb, raised around the core with a combination of wooden palisades and earthen ramparts.